Efficacy and safety of adding immune checkpoint inhibitors to first-line standard therapy for recurrent or advanced cervical cancer: a meta-analysis of phase 3 clinical trials - Zhang, Xinmiao; Shen, Jinhai; Huang, Mengfan; Li, Rongxia (Frontiers in Immunology, 2024)
BackgroundImmune checkpoint inhibitors (ICIs) combined with standard therapy (ST) have emerged as a novel treatment strategy for recurrent or advanced cervical cancer (r/a CC). However, the available data from phase 3 clinical trials have yielded mixed results. This study aims to evaluate the therapeutic efficacy and safety of adding ICIs to ST in the treatment of r/a CC.MethodsData from four phase 3 clinical trials (KEYNOTE-826, CALLA, BEATcc, and ENGOT-cx11/GOG-3047/KEYNOTE-A18), involving 2,857 patients, were analyzed. Meta-analyses were conducted to combine hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), odds ratios (ORs) for the objective response rate (ORR), and relative risks (RRs) for adverse events (AEs).ResultsThe addition of ICIs to ST significantly improved PFS (HR, 0.67; 95% CI, 0.60-0.75), OS (HR, 0.66; 95% CI, 0.58-0.75), and ORR (OR, 1.48; 95% CI, 1.13-1.94) compared to ST alone. However, there was a modest increase in grade 3-5 AEs (RR, 1.08; 95% CI, 1.03-1.13) with the combined therapy.ConclusionThis meta-analysis indicates that the combination of ICIs with ST in the treatment of r/a CC not only demonstrates superior efficacy over ST alone but also maintains a comparable toxicity profile, offering strong evidence for an effective and relatively safe treatment approach for managing this disease.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024593895.